Related Factors of Antiretroviral Adherence in HIV/AIDS Patients at one of the Community Health Centers in Malang City: Faktor yang Mempengaruhi Kepatuhan Pengobatan Antiretroviral pada Pasien HIV/AIDS di Salah Satu Puskesmas di Kota Malang - Putra, Dimas Setyadi; Puspitasari, Irma Melyani; Alfian, Sofa Dewi; Sari, Aisha Maulidya; Hidayati, Ika Ratna; Atmadani, Rizka Novia (Brawijaya University, 2023)
Introduction: HIV or Human Immunodeficiency Virus has become a serious global problem due to increased yearly infections. People living with HIV/AIDS (PLHIV) must take antiretrovirals (ARV) to improve their quality of life, so adherence is the main focus of therapy. Objective: This study aims to determine the factors that influence of adherence to ARV treatment in PLWHA at one of the Community Health Centers in Malang City. Methods: This study used a descriptive cross-sectional analysis method by collecting data using the Adherence to Refills and Medication Scale (ARMS) questionnaire during the February-March 2021 period at one of the Community Health Centers in Malang City and the data was analyzed using multivariate regression to determine the factors that influence adherence to ARV treatment. Results: This study involved 85 PLHIV patients. A total of 59 people (69.4%) were included in the compliant category on antiretroviral treatment. Multivariate analysis showed that men were 4 times more likely to be disobedient (p=0.022; OR = 4.922; 95% Cl = 1.261 – 19.208), while respondents with school education were less likely to be disobedient p=0.007 ; OR = 0.118; 95% Cl = 0.025 – 0.558). As for age, marital status, and employment status did not have a significant effect on adherence to ARV treatment. Conclusion: Gender is the most dominant factor in influencing adherence where male patients are 4 times more likely to be non-adherent compared to female patients.